2008
DOI: 10.1124/jpet.108.141531
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Selectivity of D2Dopamine Receptors Is Modulated by Changes in Local Dynamics Produced by Sodium Binding

Abstract: We have uncovered a significant allosteric response of the D 2 dopamine receptor to physiologically relevant concentrations of sodium (140 mM Our findings demonstrate how key interactions can be modulated by occupancy at an allosteric site and are consistent with a mechanism in which sodium binding enhances the affinity of selected ligands through dynamic changes that increase accessibility of substituted benzamides and 1,4-DAP ligands to the orthosteric site and accessibility of 1,4-DAPs to V2.61(91)F.Sodium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 30 publications
2
35
0
Order By: Relevance
“…Subsequent studies suggested that the effect of Na 1 likely involves modulation of the conformational state of the receptor (Simon and Groth, 1975), and that the binding of certain antagonists can actually be potentiated by the ion (Appelmans et al, 1986), one of the key characteristics exploited in the biochemical identification and validation of inverse agonism (Costa and Herz, 1989). These observations were soon extended to numerous other class A GPCRs, including those for biogenic amines, nucleosides, peptides, and lipids (Ericksen et al, 2009;Liu et al, 2012;Katritch et al, 2013); Fig. 4A shows an example of opposing effects of Na 1 on the binding of an agonist (quinpirole) and inverse agonist (epidepride) at the dopamine D 2 receptor (Neve, 1991), which is consistent with the expectations of behavior within a two-state receptor model (Christopoulos, 2014).…”
Section: Ions As Allosteric Modulatorsmentioning
confidence: 90%
“…Subsequent studies suggested that the effect of Na 1 likely involves modulation of the conformational state of the receptor (Simon and Groth, 1975), and that the binding of certain antagonists can actually be potentiated by the ion (Appelmans et al, 1986), one of the key characteristics exploited in the biochemical identification and validation of inverse agonism (Costa and Herz, 1989). These observations were soon extended to numerous other class A GPCRs, including those for biogenic amines, nucleosides, peptides, and lipids (Ericksen et al, 2009;Liu et al, 2012;Katritch et al, 2013); Fig. 4A shows an example of opposing effects of Na 1 on the binding of an agonist (quinpirole) and inverse agonist (epidepride) at the dopamine D 2 receptor (Neve, 1991), which is consistent with the expectations of behavior within a two-state receptor model (Christopoulos, 2014).…”
Section: Ions As Allosteric Modulatorsmentioning
confidence: 90%
“…Host cell lines lacking the receptor subtypes of interest were used to stably express individual cloned receptors as described by us previously (Ericksen et al, 2009). The human embryonic kidney (HEK293) cell type was used for the expression of the following receptors: cloned rat dopamine D 2 and D 4 receptors, human a 2C receptor, and human serotonin 5-HT 1A , 5-HT 2A , and 5-HT 2C receptors.…”
Section: Preparation Of Membranes For Radioligand Binding Assaysmentioning
confidence: 99%
“…CHO, Att20, and CHO-K1 cells were host cell types for expressing cloned human dopamine D 1 , dopamine D 3 , and human histamine H 1 receptors, respectively, and the MCF-7 cell type was the host for expressing the cloned human Sigma 1 receptor. The expression level of the different receptor subtypes in individual clonal lines was determined by radioligand saturation isotherm binding utilizing rapid filtration techniques and cell membrane preparation as described previously (Ericksen et al, 2009). Permeabilized platelets from New Zealand albino rabbit was the source of VMAT2 (Cesura et al, 1990).…”
Section: Preparation Of Membranes For Radioligand Binding Assaysmentioning
confidence: 99%
“…With the exceptions of N- [2-[2-hydroxy-3-[4-(4-hydroxy-3-methoxyphenyl) Membrane Preparation. Wild-type and mutant rat D4 dopamine receptors were stably expressed in HEK239 cells by using the same methodology as described previously (Kortagere et al, 2004;Ericksen et al, 2009). In brief, plasmid DNA containing the receptor and a resistance gene for G418 were transfected by CaPO 4 precipitation into a low confluence of HEK293 cells.…”
Section: Methodsmentioning
confidence: 99%